The quantile domain volatility shock transmission between carbon emission trading system and European emerging stock markets: Practical implications for portfolio optimization - Abdullah A. Aljughaiman; Mosab I. Tabash; Suzan Sameer Issa; Abdulateif A. Almulhim (PLoS ONE, 2026)
This article explores the asymmetrical volatility shock spillovers between European Carbon Emission Trading System (EU-ETS) and European emerging economies’ stock markets by using the Quantile-based Vector Auto Regression (QVAR), “Extended Joint” connectivity framework. The QVAR approach suggested that a volatility shock in the EU-ETS transmitted higher conditional volatility shocks of 19.37%, 17.86%, 18.9%, 19.49% and 19.76% towards the equity markets of Czech Republic, Slovakia, Greece, Hungary and Poland at the bullish quantiles ( τ = 0 . 9 5 ) as compared with bearish ( τ = 0 . 0 5 ) and moderate ( τ = 0 . 5 0 ) volatility conditions. The overall aggregated measure of the volatility shock spillovers between EU-ETS and equity markets is approximately 30.63% and 29.43% at bearish and moderate quantiles, respectively as compared with 88.01% at the bullish volatility conditions. The QVAR results also indicate that Greece, Poland, and Hungary (Slovakia) are structurally more (less) exposed to bearish and moderate EU-ETS volatility shocks. Therefore, Slovakia serves as a stabilizing asset within a multi-country portfolio, especially during bearish, bullish and moderate EU-ETS volatility conditions. Therefore, Slovakian equities remain least affected even in bullish EU-ETS volatility regime, functioning as an optimal low-beta hedge component and thereby help in reducing portfolio-wide shock amplification. Therefore, at the upper quantiles, where volatility transmission becomes uniformly elevated across all markets, fund managers take into account the volatility-convergence arbitrage, capitalizing on Slovakian equities persistent weaker sensitivity. However, stress testing frameworks should incorporate quantile-dependent country-specific volatility loadings, with higher coefficients for Greece, Poland, and Hungary across lower and moderate EU-ETS volatility shocks. In the terms of macro-prudential policy adjustments, equity market regulators and policy makers in Greece, Poland, and Hungary should strengthen transition-risk buffers during bearish and moderate ETS volatility shock diffusion. Finally, the DCC-GARCH- t copula findings suggested that portfolio managers can overweight Czech Republic and Slovakia equities during periods of rising EU-ETS volatility and use them as low-beta components in mixed carbon–equity portfolios.